Strategies for Fault Propagation and Recovery in Urban Rail Transit Systems Using Complex Network Analysis - Yang, Wei; Mu, Liping (International Journal of Informatics and Information Systems, 2023)
Urban rail transit is a vital part of the transportation infrastructure in cities, becoming a preferred choice for an increasing number of commuters. Nevertheless, the occurrence of station failures due to emergencies poses a significant challenge that can disrupt the entire transit system. This situation underscores the necessity for improved resilience and effective recovery strategies within urban rail systems. This research addresses the critical issue of how to effectively control fault spread and swiftly restore system operations after a failure. Utilizing metro network data from Gaode maps and leveraging complex network theory, we constructed a network topology model to analyze these dynamics. Our investigation focused on the patterns and mechanisms of fault propagation within the metro network, both in the absence and presence of recovery interventions. The primary objective was to uncover the fundamental principles governing fault spread in urban rail systems. Through detailed data analysis and the development of recovery models, we aimed to offer valuable insights into reducing the impact of failures and enhancing the overall reliability of urban rail transit. The study concludes with a simulation of four distinct recovery strategies, providing a comparative assessment of their effectiveness. These findings are essential for urban planners, transit authorities, and policymakers in crafting strategies to mitigate the effects of emergencies on urban rail transit. Ultimately, the research contributes to ensuring a resilient and efficient transportation system that can support the demands of a growing urban population.